2013
DOI: 10.1534/genetics.113.150227
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Predictability of Interconnected Biparental Maize Populations

Abstract: Intense structuring of plant breeding populations challenges the design of the training set (TS) in genomic selection (GS). An important open question is how the TS should be constructed from multiple related or unrelated small biparental families to predict progeny from individual crosses. Here, we used a set of five interconnected maize (Zea mays L.) populations of doubled-haploid (DH) lines derived from four parents to systematically investigate how the composition of the TS affects the prediction accuracy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
179
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(206 citation statements)
references
References 44 publications
22
179
5
Order By: Relevance
“…As all dent families are equally connected through one common parent, no relevant differences in linkage phases were observed between UH304 and the other dent families. Thus, differences in linkage phases as it has been suggested in other outlying cases of low prediction performance (Riedelsheimer et al 2013;Würschum et al 2013) cannot be a reason for the poor prediction performance here. UH304 was the only Iodent founder line within the dent pool and thus less related to the other founder lines.…”
mentioning
confidence: 48%
See 1 more Smart Citation
“…As all dent families are equally connected through one common parent, no relevant differences in linkage phases were observed between UH304 and the other dent families. Thus, differences in linkage phases as it has been suggested in other outlying cases of low prediction performance (Riedelsheimer et al 2013;Würschum et al 2013) cannot be a reason for the poor prediction performance here. UH304 was the only Iodent founder line within the dent pool and thus less related to the other founder lines.…”
mentioning
confidence: 48%
“…Including additional lines from the opposite pool (i.e., unrelated families with different linkage phases) to the estimation set of LOCO-CV had no impact on predictive abilities in our study (results not shown). This might be surprising as one might expect that including unrelated families to the estimation set should lead to a decrease of prediction performance as different linkage phases between markers and QTL might exist that in turn lead to wrongly estimated marker effects (Riedelsheimer et al 2013). However, as the relationship between dent and flint lines observed by markers is close to zero, as seen on the heatmap of the realized kinship, the GBLUP model does not borrow information from lines of the other pool for prediction of lines from the same pool.…”
mentioning
confidence: 99%
“…Previous studies have shown that prediction accuracy is impaired when performing genomic selection across connected biparental populations (Zhao et al 2012;Riedelsheimer et al 2013). This may be explained at least partially by epistatic effects as the genetic relatedness across connected populations may be better exploited by modeling epistasis in addition to additive effects.…”
Section: Enhancing Prediction Accuracy Across a Biparental Populationmentioning
confidence: 99%
“…In addition, the efficiency and accuracy with which superior lines can be predicted also depend on the size of the reference population (Jannink et al, 2010;Lorenz et al, 2011). The genetic relatedness or population structure (Saatchi et al, 2011;Riedelsheimer et al, 2013;Wray et al, 2013) may result in overestimating the heritability of the traits (Price et al, 2010;Visscher et al, 2012;Wray et al, 2013). The population structure of the training population can be determined with greater accuracy using genome wide SNPs compared with the simple sequence repeats and SNP arrays (Isidro et al, 2015).…”
Section: Genotyping Platforms Training Populations and Statistical Mmentioning
confidence: 99%